Two new species of Neocarus (Acari: Opilioacaridae) from Piauí and Rio de Janeiro, Brazil, with remarks on integument and seta shape as characters - De Araújo, Marcel Santos; Palma, Antonella Di; Ochoa, Ronald; Fazzio Feres, Reinaldo José [UNESP]; Marigo, Thaís Coimbra; Penteado-Dias, Angelica Maria (Systematic and Applied Acarology Society, 2022)
Two new opilioacarid species from Northeast and Southeast of Brazil are described. Neocarus setilatussp. nov. from a gallery forest in Piauí and Neocarus marambaiasp. nov. from a restinga area in Rio de Janeiro. Both species have the similar starshaped integument character and smaller, broader setae. We discuss the importance of these characters with systematic value and present an updated taxonomic key for the genus Neocarus.
Keywords: Neotropical; Opilioacarida; Restinga